Research on the Capital Adequacy Ratio, Good Governance and Leverage in Islamic Banking - Uckun, Nurullah; Ölçen, Olcay (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Purpose: This research mainly proposes to investigate the Islamic Banks considering Capital Adequacy Ratio (CAR) and corporate governance for 13 Muslim countries and the United Kingdom. Method: Econometric panel data analysis is utilized for this research after necessary tests are used. The research data is taken from the World Bank and Islamic Financial Services Board web page. Results: According to research results, a %1 augmentation in political stability causes a 0.0518 increase in Capital Adequacy Ratio (CAR), a %1 rise in regulator quality causes a 0.0416 increase in Capital Adequacy Ratio (CAR), a %1 increase in Capital to Asset Ratio causes to 0.708 increase in CAR (index). According to the research model, ROE, Control of Corruption, Government Effectiveness, and Political stability do not in a significant statistical relationship with Capital Adequacy Ratio. Implication: The findings of this study suggest that there can be interpretation differences between conventional banks and their Islamic counterparts regarding banking financial management. In the regulative dimension, the existence and efforts of Basel regulations and the Islamic Financial Services Board develop in parallel with this context on the subject of CAR and other important dimensions of Islamic Banks. Originality: This paper contributes to Islamic finance literature by integrating governance and leverage variables into a unified model for assessing CAR